Question
upstudy study bank question image url

Consider the line \( y=\frac{3}{7} x+6 \). Find the equation of the line that is parallel to this line and passes through the point \( (-9,-5) \). Find the equation of the line that is perpendicular to this line and passes through the point \( (-9,-5) \). Note that the ALEKS graphing calculator may be helpful in checking your answer. Equation of parallel line: Equation of perpendicular line:

Ask by Sherman Schmidt. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Parallel line equation: \( y = \frac{3}{7}x - \frac{8}{7} \) Perpendicular line equation: \( y = -\frac{7}{3}x - 26 \)

Solution

We start with the given line:   y = (3/7)x + 6 To find the parallel line that passes through (-9, -5), note that parallel lines have the same slope. Thus the parallel line also has a slope of 3/7. Using the point-slope form of a line:   y - y₁ = m(x - x₁) where (x₁, y₁) = (-9, -5) and m = 3/7, we have:   y - (-5) = (3/7)(x - (-9))   y + 5 = (3/7)(x + 9) Now, solving for y:   y = (3/7)(x + 9) - 5   y = (3/7)x + (27/7) - 5 Convert 5 to sevenths (5 = 35/7):   y = (3/7)x + (27/7 - 35/7)   y = (3/7)x - (8/7) Thus, the equation of the parallel line is:   y = (3/7)x - (8/7) Next, to find the perpendicular line that passes through (-9, -5), the slope of the perpendicular line is the negative reciprocal of the original line’s slope. Since the original slope is 3/7, the perpendicular slope is:   m = -7/3 Using the point-slope form again with m = -7/3:   y - (-5) = (-7/3)(x - (-9))   y + 5 = (-7/3)(x + 9) Now, solving for y:   y = (-7/3)(x + 9) - 5   y = (-7/3)x - (7/3)*9 - 5   y = (-7/3)x - 21 - 5   y = (-7/3)x - 26 Thus, the equation of the perpendicular line is:   y = (-7/3)x - 26 Summary: • Equation of the parallel line: y = (3/7)x - (8/7) • Equation of the perpendicular line: y = (-7/3)x - 26

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find a parallel line, we know it will have the same slope as the original line. The slope from the equation \( y=\frac{3}{7} x+6 \) is \( \frac{3}{7} \). Using the point \( (-9,-5) \), we can apply the point-slope form of a line, \( y - y_1 = m(x - x_1) \): \[ y - (-5) = \frac{3}{7}(x - (-9)) \] This simplifies to: \[ y + 5 = \frac{3}{7}(x + 9) \] Distributing and rearranging gives: \[ y = \frac{3}{7}x + \frac{27}{7} - 5 \] Converting \( -5 \) to a fraction yields \( -\frac{35}{7} \), so: \[ y = \frac{3}{7}x - \frac{8}{7} \] Equation of the parallel line: \( y = \frac{3}{7}x - \frac{8}{7} \) For the perpendicular line, we need the slope to be the negative reciprocal of \( \frac{3}{7} \), which is \( -\frac{7}{3} \). Again, using the point-slope form: \[ y - (-5) = -\frac{7}{3}(x - (-9)) \] This simplifies to: \[ y + 5 = -\frac{7}{3}(x + 9) \] Distributing and rearranging gives: \[ y = -\frac{7}{3}x - 21 + 5 \] Converting \( 5 \) to a fraction yields \( \frac{15}{3} \), so: \[ y = -\frac{7}{3}x - \frac{21}{3} + \frac{15}{3} \] Thus, we have: \[ y = -\frac{7}{3}x - \frac{6}{3} \] This simplifies to: \[ y = -\frac{7}{3}x - 2 \] Equation of the perpendicular line: \( y = -\frac{7}{3}x - 2 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy